A Tandem Array of ent-Kaurene Synthases in Maize with Roles in Gibberellin and More Specialized Metabolism . Issue 2 (30th November 2015) - Fu, Jingye; Ren, Fei; Lu, Xuan; Mao, Hongjie; Xu, Meimei; Degenhardt, Jörg; Peters, Reuben J.; Wang, Qiang
Abstract : Characterization of a maize tandem gene array reveals three kaurene synthases with varied roles in gibberellin and phytoalexin metabolism. Abstract: While most commonly associated with its role in gibberellin phytohormone biosynthesis, ent -kaurene also serves as an intermediate in more specialized diterpenoid metabolism, as exemplified by the more than 800 known derived natural products. Among these are the maize kauralexins. However, no ent -kaurene synthases (KS s) have been identified from maize. The maize gibberellin-deficient dwarf-5 ( d5 ) mutant has been associated with a loss of KS activity. The relevant genetic lesion has been previously mapped, and was found here to correlate with the location of the KS -like gene ZmKSL3 . Intriguingly, this forms part of a tandem array with two other terpene synthases (TPS s). Although one of these, ZmTPS1, has been previously reported to encode a sesquiterpene synthase, and both ZmTPS1 and that encoded by the third gene, ZmKSL5, have lost the N-terminal γ -domain prototypically associated with KS (L)s, all three genes fall within the KS (L) or TPS -e subfamily. Here it is reported that all three genes encode enzymes that are targeted to the plastid in planta, where diterpenoid biosynthesis is initiated, and which all readily catalyze the production of ent -kaurene. Consistent with the closer phylogenetic relationship of ZmKSL3 with previously identified KS s from cereals, only transcription of this gene is affected in d5 plants. On the other hand, the expression of all three of these genes is inducible, suggesting a role in more specialized metabolism, such as that of the kauralexins. Thus, these results clarify not only gibberellin phytohormone, but also diterpenoid phytoalexin biosynthesis in this important cereal crop plant.